Islam Cerdas di Ruang Digital: Urgensi Peran Mahasiswa dalam Menebar Jala Moderasi Beragama di Media Sosial - Ali Mursyid Azisi; Lailiyah Qotrunnada; M. Abd. Fatah; Akhmad Uzaimy Zain (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2022)
This article examines the urgency of the role of students in spreading the net of religious moderation in the virtual world (digital). Considering the growing movement of extremist/radical/terrorist groups in the digital space, there needs to be a balance or even dominance of polite (moderate) Islamic doctrine in an effort to maintain the stability of socio-religious life. Moreover, the rapid development of technology, digital media is now a public consumption for communication, sharing, and accessing scientific sources, including in conveying an increasingly varied religious expression. Therefore, in this article, we try to explore the important contribution that generation Z students can make as productive consumers of social media in an effort to spread the net of religious moderation (smart Islam) in the digital space (air). First, being able to read what social media platforms are most in demand by the public. Second, being able to create creative content about moderate da'wah and interesting to watch. Third, continue to maintain the consistency of da'wah in the digital space. Fourth, fresh innovations by students are able to give a new color to the preaching of religious moderation in Indonesia. A qualitative approach is a step that is applied in systematically compiling this article. By utilizing the library research method with relevant sources and utilizing social media channels as examples of content references that are studied in detail, later it will be related to how reading opportunities for students in spreading the symbols of religious moderation in the digital space can be realized. In this way, guarding religious moderation and countering hardline groups does not only involve teachers, experts, and clergy, but also involves students as the golden generation of moderates.